Prática como componente Curricular e estágio supervisionado na formação de professores de Educação Física - Maffei, Willer Soares [UNESP] (2014)
This study aims to investigate the main issues presented in the literature relating to teacher training during the period 2005/2014. Particular attention is paid to articles that address the Supervised Training and Practice as a Curriculum Component. For the analysis of the articles from the literature, the technique of Content Analysis was used. The results showed that the potential which is attributed to these curricular components depends on the ability to put the trainee teacher in touch with the experience of being a teacher, whilst enabling the approach of the training content to be consistent with professional practice. The technical and fragmented curriculum for training and the extensive content in the disciplines, limited by outmoded practices, is presented as a barrier against this occurring. This shows a discrepancy in the proposed training between the pedagogical design of the course and, what is actually designed as concrete action in its development.